Review of the Characteristics of School-Based Integrated Mental Health and Substance Use Prevention Programs for Adolescents Evaluated Through Clinical Trials Between 2016 and 2026 - Kyung-Young Hong; Jihye Shin (Children, 2026)
Background/Objectives: Adolescent substance use and mental health problems frequently co-occur and share common risk and protective factors. Some school-based prevention programs address substance use and mental health within an integrated approach. However, the characteristics and intervention components of these integrated approaches remain insufficiently understood. This review aimed to describe the program characteristics of school-based integrated mental health and substance use prevention programs for adolescents that were evaluated in randomized or cluster randomized controlled trials (RCTs/cRCTs), with particular attention to their intervention components, delivery approaches and prevention strategies. Methods: This review used a structured approach comprising a systematic literature search, predefined eligibility criteria, independent study selection, standardized data extraction and coding, and descriptive synthesis. Electronic databases (PubMed, Embase, Cochrane Library, CINAHL, PsycINFO, KMbase, KoreaMed, ScienceON, DBpia, KISS, RISS, and PQDT) were searched for studies published between January 2016 and April 2026. Studies were eligible if they were randomized or cluster randomized controlled trials evaluating school-based interventions that incorporated both substance use prevention and mental health promotion components among adolescents. Data were extracted and synthesized descriptively at the program level to summarize program characteristics and intervention components. Results: Fifteen studies representing 10 unique programs were included. Mental health literacy was identified in 5 programs and emotional regulation in 4. Drug literacy and resistance skills were each identified in 6 programs, alcohol prevention in 5, and cannabis prevention in 4. A descriptive cross-domain analysis identified overlapping patterns involving literacy, self-regulation, help-seeking, social competence, peer support, and family-focused approaches rather than mutually exclusive program types. Conclusions: The school-based integrated prevention programs evaluated in randomized or cluster randomized controlled trials and included in this review combined substance use prevention with mental health promotion components, including psychosocial skill development, peer support, and, in one program, a family-focused approach. The descriptive synthesis of program characteristics provides an initial basis for understanding the diverse approaches used in integrated school-based prevention and may inform the future design and evaluation of programs targeting adolescent mental health and substance use.